Harmonizing Narratives: A Qualitative Exploration of the Life Experiences and Challenges Faced by Music Core Groups in the Cebu Province Music Industry - Almaden, Antoniette M.; Ocampo, Alex P.; Delantar, Alexander Franco A. (Future Science / FSH-PH Publications, 2024)
This study examined the intricate life experiences and challenges faced by music core groups within the ever-changing Cebu Province Music Industry. A qualitative multiple-case study technique was employed to harmonize narratives by revealing common experiences and challenges. Furthermore, the research aimed to provide interventions that might assist music core groups in effectively addressing their difficulties. Through cross-case analysis, the study uncovered underlying themes, such as Evolution and Growth, Challenges, Support Systems, and Passion and Personal Fulfillment, that transcended the boundaries of different music core groups. The text explored distinct variations in terms of Business Orientation, Role and Artistic Identity, Artistic Foundation, and Creative Liberty. Coping strategies were found to be essential for building resilience and took several forms, including faith, self-care, diversion, economic bargaining skills, continual learning, and community participation. The discovery of these coping methods offered valuable insights into the resilience techniques utilized by music core groups. Moreover, the research extended beyond mere inquiry and put forth interventions designed to assist music core groups in surmounting their difficulties. This research provided practical suggestions to aid stakeholders, policymakers, and industry participants in improving the sustainability and well-being of the dynamic music community in Cebu Province. These recommendations aimed to build specific initiatives for this purpose.